Omar Tugrul Inancer’s Detections on Some Turkish Idioms and Metaphores About The Influence of Islamic Sufism on Daily Life - Derya Kılıçkaya (Tasavvuf Araştırmaları Enstitüsü Dergisi, 2023)
Omar Tugrul Inancer, who grew up in a family and environment with Ottoman remnants, is a person who received his mystic education and manners by personally experiencing it from the environment where he grew up. He was a Sūfī, a man of faith who was “bred at the bottom of the knee”, so to speak, of the perfect masters of his time, who were considered important. Although he described himself as “sofimeshrep” in order not to use his Sūfī identity either because of the current conditions or as an advertising element, his qualification as a murshid-e-kamil has always attracted attention. The hadith, “Believers do not die but rather migrate from some place to another” which is frequently mentioned in forty hadith translations in verse was often used by Omar Tugrul Inancer. He himself “migrated” to the hereafter on September 4, 2022. Inançer, who is a very good orator, has many works written in conversational style. It is among the aims of this article to evaluate the mysticism and daily life in his book, Vakte Karşı Sözler (Words Against Time), the first edition of which was published in 2006, in terms of our language. The book essentially consists of translating a Sūfī conversation carried out by Ayse Sasa Oran with Omar Tugrul Inancer. The audio recording of this conversation was later deciphered by Berat Demirci and was also made into a book. There are two titles in this book on the subject of Sufism and daily life. The first of these is the conversation that took place around the questions asked by Ayse Sasa. The second was held in 2003 at the Turkish Literature Foundation. This is the text of the conference given by Omar Tugrul Inancer. In this study, the effects of some mystical words in our language will be evaluated with the determinations of İnançer, based on both texts.